Is the Bandgap of Bulk PdSe2 Located Truly in the Far‐Infrared Region? Determination by Fourier‐Transform Photocurrent Spectroscopy - Wataru Nishiyama; Tomonori Nishimura; Masao Nishioka; Keiji Ueno; Satoshi Iwamoto; Kosuke Nagashio (Advanced Photonics Research, 2022)
2D bulk PdSe2, a group 10 noble metal dichalcogenide, is recognized as a newly found far‐infrared material with a bandgap energy (E G) of ≈0.05 eV and thus has attracted much attention as an optoelectronic material. However, the bandgap energy of bulk PdSe2 is the subject of a controversial debate as a middle bandgap of ≈0.3 eV is also reported by electrical transport measurements. Although determining E G by optical absorption measurement is essential, the difficulty lies in the weak absorption caused by indirect transition. Herein, it is quantitatively estimated that the indirect E G of bulk PdSe2 is indeed 0.5 eV at 40 K based on the highly sensitive spectroscopic method of Fourier‐transformation photocurrent spectroscopy. Herein, it is suggested that the potential application of PdSe2 should be properly selected.